Urethanases for the Enzymatic Hydrolysis of Low Molecular Weight Carbamates and the Recycling of Polyurethanes. Issue 9 (24th January 2023) - Branson, Yannick; Söltl, Simone; Buchmann, Carolin; Wei, Ren; Schaffert, Lena; Badenhorst, Christoffel P. S.; Reisky, Lukas; Jäger, Gernot; Bornscheuer, Uwe T.
Abstract: Enzymatic degradation and recycling can reduce the environmental impact of plastics. Despite decades of research, no enzymes for the efficient hydrolysis of polyurethanes have been reported. Whereas the hydrolysis of the ester bonds in polyester‐polyurethanes by cutinases is known, the urethane bonds in polyether‐polyurethanes have remained inaccessible to biocatalytic hydrolysis. Here we report the discovery of urethanases from a metagenome library constructed from soil that had been exposed to polyurethane waste for many years. We then demonstrate the use of a urethanase in a chemoenzymatic process for polyurethane foam recycling. The urethanase hydrolyses low molecular weight dicarbamates resulting from chemical glycolysis of polyether‐polyurethane foam, making this strategy broadly applicable to diverse polyether‐polyurethane wastes. Abstract : We made a metagenome library and discovered urethanases that can hydrolyse a broad range of industrially relevant dicarbamates resulting from glycolysis of polyether‐polyurethanes. This enables a two‐step chemo‐enzymatic recycling procedure consisting of glycolysis followed by enzymatic hydrolysis, allowing both the polyether polyols and the aromatic diamines to be recovered from polyether‐polyurethane foams.